تأثیر مجموعات المکتبة المرکزیة بجامعة القاهرة فى البحث العلمى فى تخصص المکتبات والمعلومات : دراسة تحلیلیة - د.سرفیناز أحمد حافظ (المجلة الدولية لعلوم المكتبات والمعلومات)
The study aims to verify the impact of the central library collection at CairoUniversity in preparing theses in the field of library, Archives and informationtechnology based on ISO standard No. 16439 dated 2014 concerning the impactof libraries. The study concerned with approved theses in the years 2016/2017,applying the citation analysis approach in order to measure the impact of theCairo University Central Library in serving specialized scientific research.The study tried to answer the following questions: first of all the extent towhich the Central Library of Cairo University fulfills the needs of postgraduatestudents in the field of libraries and information through its printed and electronicresources. Secondly researchers’ satisfaction with the services provided throughthe Central Library. Thirdly what are the information sources has a weaknesspoints in the Central Library. Finally, practice of acknowledgment by researchersof the libraries role, databases, digital library, etc.in the methodological introduction to the approved thesis. The studyanalyzed (3382 citations).The study reached a number of results, first of all thatthe Central Library collections influenced in the total citations in theses subjectmatter of the study by 41%, and there for it has some weakness in the coveragewhich is more than half the volume of materials cited, and which calls for thelibrary to reconsider the policy of collection development to increase its influencein pushing the scientific research movement in the field of libraries, Archives andinformation technology. The results indicate that there is a weakness in the libraryforeign collections.  In addition Conference papers came in the highest types of informationsources that the beneficiaries and researchers have difficulty in reaching. On theother hand, the study showed clear variation in the commitment of researchers tothe quality of citations and accuracy of bibliographic data, which impedes thequality of access to information sources cited, and negatively affects the Impactof the central library collections. The study recommended that the field of Impactof libraries, especially university and research  Therefore, it is recommendedto increase the number of studies applied to the standard. The study alsorecommended working in accordance with the research plans of the scientificdepartments to keep up with their collections for the new research directions, aswell as recommended to encourage researchers to use Reference managersSoftware such as RefWorks, EndNote, Mendeley to ensure the accuracy andstandardization of source description data.